The Sensitivity of Structural Labor Supply Estimations to Modeling Assumptions - Max Löffler; Andreas Peichl; Sebastian Siegloch (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
There is still considerable dispute about the magnitude of labor supply elasticities. While differences in estimates especially between micro and macro models are recently attributed to frictions and adjustment costs, we show that the variation in elasticities derived from structural labor supply models can also be explained by modeling assumptions. Specifically, we estimate 3,456 different models on the same data each representing a plausible combination of frequently made choices. While many modeling assumptions do not systematically affect labor supply elasticities, our controlled meta-analysis shows that results are very sensitive to the treatment of hourly wages in the estimation. For example, different (sensible) choices concerning the modeling of the underlying wage distribution and especially the imputation of (missing) wages lead to point estimates of elasticities between 0.2 and 0.65. We hence conclude that researchers should pay more attention to the robustness of their estimations with respect to the wage treatment.
Keywords: C25; C52; H31; J22; 330; Labor supply; elasticity; random utility models; wages